Decision-Making Under Ambiguity or Risk in Individuals With Alzheimer’s Disease and Mild Cognitive Impairment - Sun, Tingting; Xie, Teng; Wang, Jing; Zhang, Long; Tian, Yanghua; Wang, Kai; Yu, Xin; Wang, Huali (Frontiers in Psychiatry, 2020)
Background Making advantageous decisions is essential in everyday life. Our objective was to assess how patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) make decisions under conditions of ambiguity or risk. In addition, the study also aimed to examine the relationship between decision-making competence and memory and executive function. Methods Patients with MCI (n = 36) and AD (n = 29) and healthy elderly controls (HC, n = 34) were recruited from the memory clinic. All subjects were administered a comprehensive neuropsychological battery test. We used the Iowa Gambling Task (IGT) to measure decision-making under ambiguity and the Game of Dice Task (GDT) to measure decision-making under risk. Pearson’s correlation was used to examine the relationship between the performance of IGT and GDT with delayed recall and the Stroop test. Results In the GDT, MCI and AD patients presented similar performance but showed different patterns when compared with the HC group. The proportion of those making advantageous choices was lower in the AD group than in the HC group (p = 0.01), while the MCI and HC groups did not differ (p = 0.14). Meanwhile, concerning the ratio of accepting negative feedback, the AD (p < 0.01) group was significantly different from the HC patients, but the MCI (p = 0.06) and HC groups did not differ. In the IGT, MCI and AD patients selected randomly from advantageous and disadvantageous decks (p = 0.94 and p = 0.54), showing no significant change in performance over time. In contrast, the HC group made increasingly frequent advantageous selections over time (p = 0.04). Furthermore, the proportion of advantageous decision-makers for the GDT had a linear relationship with delayed recall of the Hopkins Verbal Learning Test and Stroop color words (p < 0.01 and p < 0.01, respectively). Conclusion Our findings suggest that decision-making ability under ambiguity is compromised in MCI and AD, and the decision-making under risk is only impaired in AD. Reduced decision-making performance under risk is closely correlated with lower executive functions and memory.